Antena Transceiver Untuk Komunikasi Bluetooth ISM-Band Dengan Metode Complementary Split Ring Resonator - Yustina Wahyu Andika; Hasanah Putri; Dwi Andi Nurmantris (Universitas Syiah Kuala, 2018)
A Bluetooth was developed as a means for short-range communications. However, the limited range of Bluetooth devices that tend to be narrowly led to the use of Bluetooth is less developed. Whereas, with its properties, sharing of data should be done easily and cheaply. This research has designed a transceiver antenna for Bluetooth communications that works at a frequency 2.4 GHz ISM-band. The antenna is designed in the form of a microstrip antenna with Complementary Split Ring Resonator (CSRR) methods to reduce the dimensions of the antenna. The result of this research is a form of a transceiver antenna that works at a frequency of 2.398 GHz to 2.47 GHz with -30.815 dB return loss and VSWR worth 1,074. The resulting radiation pattern is a directional pattern with a gain of 11.84 dB. Implementation of the CSRR method can reduce antenna dimension by 53.47 %.